The characterization of Pyrite from the Ventersdorp contact Reef of the Kloof Gold Mine in the Witwatersrand Basin in South Africa - Merkle, R.K.W. (Roland Karl Willi), 1954- (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.